Peranan Satuan Polisi Pamong Praja Dalam Melaksanakan Penegakan Peraturan Daerah - Elza Syarief; Wagiman Wagiman; Raja Syaiful Anwar (Journal of Judicial Review, 2014)
One of the officers who served as a supporter of the implementation of the administration was Civil Service Police Unit (municipal police). Civil Service Police Unit (municipal police) was a device that assisted local governments in the implementation of regional heads running of the government and as a guard or vanguard in the field of public peace and order. To assist in the establishment of the local regulations and implementation of public order and peace of the community formed Civil Service Police Unit (municipal police). Keywords: Indonesian Government RegulationNo.6of 2010 on theSatuan Polisi Pamong Praja (Satpol PP, The role ofmunicipal police, Implementation ofSOP